CHATBOT BERBASIS NLP UNTUK REKOMENDASI PRODUK SKINCARE LOKAL PADA TELEGRAM - Agustin, Syafira Cessa; Syafina, Prilia Hashifah; Rachmatin, Nida; Pratama Yusuf, Ajif Yunizar (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
This research applies a Natural Language Processing (NLP)-based chatbot to provide recommendations for local skincare products. Telegram, as a widely used communication platform, is an ideal medium to present this innovative solution to consumers looking for appropriate skincare products. The chatbot is designed to understand the user's needs regarding skin type, and skin concerns. By utilizing artificial intelligence, the chatbot can provide personalized recommendations of suitable local skincare products, improving consumers' access to product information and facilitating the process of selecting the right product. This research is expected to make chatbot an effective tool in finding skincare products that suit the skin, as well as increasing consumer participation in supporting the local skincare industry through instant messaging platform, telegram.